TRANSFORMATION OF THE POLITICAL SYSTEM IN GEORGIA TODAY - TUKVADZE, Avtandil; JAOSHVILI, Georgi; TUKVADZE, Rati (CENTRAL ASIA AND THE CAUCASUS, 2006)
The newly independent states which arose in the post-Soviet expanse at the beginning of the 1990s immediately began transplanting to local soil the democratic constitutions and political systems officially approved in the West, particularly those with a semi-presidential and presidential rule. But the practice of the transition period showed that mere declaration of Western-style constitutions in no way means the actual formation of a corresponding political system. Introducing the principle of division of power into the Basic Law does not guarantee it will function democratically in the way theoreticians understand it and as it is currently executed in countries with a developed democracy. What actually happened in most of the transition states was that all power went to the executive bodies, and the legislative and judicial branches became their perfunctory appendages. Finding them-selves back at the helm, the former nomenklatura leaders of the communist parties of the past Union republics acted like first secretaries of the Central Committee, since they were endowed with corresponding powers. So in many post-Soviet countries, the principle of division of power turned out to be stillborn. Only the corresponding articles of the republican constitutions remind us of its formal existence.